Pelatihan Instalasi Penerangan Bagi Masyarakat Putus Sekolah di Kabupaten Manokwari - Bawan, Elias Kondorura (Fakultas Peternakan Universitas Papua, 2021)
ABSTRACT Electricity is an important part of human life. The need for electrical energy increases directly proportional to the increase in population growth. Manokwari Regency as the capital of West Papua province continues to carry out the construction of offices, housing and other public facilities from year to year that require electrical energy. Electrical installation demands professionalism and standards in accordance with the general electrical installation regulations (PUIL). This community service activity aims to train people who cannot continue their education to a higher level due to limited costs. Participants are trained to be able to carry out installation, repair installations, and open their own jobs. Community service activities are carried out in the form of training with the lecture method regarding the introduction of electrical installation tools and materials, installation practices and electrical installation wiring diagrams according to PUIL standards and direct practice in the laboratory of the Electrical engineering department of the Engineering Faculty, University of Papua. Keywords: Training; Lighting Installation, Society, PUIL. ABSTRAK Listrik merupakan bagian penting dalam kehidupan manusia. Kebutuhan energi listrik meningkat berbanding lurus dengan peningkatan pertumbuhan penduduk. Kabupaten Manokwari sebagai ibukota provinsi Papua Barat terus melaksanakan pembangunan perkantoran, perumahan dan fasilitas publik lainnya di dari tahun ke tahun yang membutuhkan energi listrik. Pemasangan instalasi listrik menuntut profesionalisme dan standar yang sesuai dengan peraturan umum instalasi listrik (PUIL). Kegiatan pengabdian kepada masyarakat ini bertujuan untuk melatih masyarakat yang tidak bisa melanjutkan pendidikan ke jenjang lebih tinggi oleh karena keterbatasan biaya. Peserta dilatih agar dapat melakukan pemasangan, perbaikan instalasi, dan membuka lapangan kerja sendiri. Kegiatan pengabdian kepada masyarakat (PKM) dilaksanakan dalam bentuk pelatihan dengan metode ceramah mengenai pengenalan alat dan bahan instalasi listrik, praktik pemasangan dan diagram pengawatan instalasi listrik sesuai standar PUIL serta praktik langsung di laboratorium jurusan teknik Elektro Fakultas teknik Universitas Papua. Kata kunci: Pelatihan; Instalasi Penerangan; Masyarakat; PUIL.